Engineering applications and analysis of vibratory motion fourth order fluid film over the time dependent heated flat plate - Mustafa, Mamat; Mohd, M.I; Shah, Q. (2017)
This article deals with the time dependent analysis of thermally conducting and Magneto-hydrodynamic (MHD) liquid film flow of a fourth order fluid past a vertical and vibratory plate. In this article have been developed for higher order complex nature fluids. The governing-equations have been modeled in the terms of nonlinear partial differential equations with the help of physical boundary circumstances. Two different analytical approaches i.e. Adomian decomposition method (ADM) and the optimal homotopy asymptotic method (OHAM), have been used for discoveryof the series clarification of the problems. Solutions obtained via two diversemethods have been compared using the graphs, tables and found an excellent contract. Variants of the embedded flow parameters in the solution have been analysed through the graphical diagrams.